Pendampingan Pengembangan Kompetensi Fotografi melalui Sertifikasi LSP bagi Mahasiswa Desain Komunikasi Visual Universitas Tarumanagara - Dhani Kurniawan; Julius Andi Nugroho (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This activity was motivated by the need for Visual Communication Design students at Tarumanagara University to acquire measurable photography competencies that align with the standards of the creative industry. Commercial photography not only requires the ability to produce visually appealing images but also demands technical and conceptual mastery, as well as expertise in composition, lighting, shooting techniques, and digital photo processing. This activity aims to guide students in preparing for and taking the LSP Photography certification as a means of strengthening their competencies based on national standards. The implementation method consists of the following stages: activity orientation, understanding competency standards, pre-assessment, production of photographic works, guidance on digital image processing, portfolio development, and evaluation of competency achievement. The results of the program showed that participants were able to produce six photographic works: “Trinket Vendors,” “Exterior of the Filosofi Kopi Coffee Shop,” “Live Music Performance at Fatahillah Park,” “The Forgotten Classics,” “Colonial Traces,” and “Behind the Calm Waters.” These works demonstrate skill mastery in composition, depth of field, lighting, shooting angles, perspective, visual clarity, and digital image processing. This mentoring program provided direct benefits to students in understanding photography industry standards, compiling portfolios, and enhancing their readiness to enter the creative workforce.